Reforms in Times of Crisis: Notes on the Greek Policy Making from Bankruptcy to COVID-19 - Balampanidis, Ioannis; Liakaki, Sotiria (European Scientific Journal, ESJ, 2021)
In this paper, an in-depth quantitative and qualitative analysis of the â€œemergencyâ€ regulation in Greece over the years of acute economic crisis and up to the COVID-19 public health crisis is performed, to examine if this kind of regulation has been too extended and whether it undermined any effective policy design. According to our working hypothesis, the â€œfast-trackâ€ legislation highlights the fragmented and somewhat erratic way of policymaking in Greece, while it also affirms the countryâ€™s limited capacity to properly initiate and implement reforms. Thus, the paper focuses on the collection and evaluation of the legislative corpus during the 2009-2021 period; its objective being, on the one hand, to evaluate whether and how much each government resorted to the invocation of urgency and on the other hand to examine the documentation and description of the legislative process vis-Ã vis the imperatives and quality criteria of Better Regulation and EvidenceBased Policy Making. At the same time, the article focuses on legislative texts of the 2020-2021 COVID-19 health crisis period. It will showcase the latter as an additional trigger aggravating the â€œurgencyâ€ element of regulation, transforming it into a persistent feature of Greek policymaking. Ergo, we examine methods and practices at the international level, focusing especially on the Evidence-Based Policy Making paradigm. Based on the analysis of the crisis regulation and international EBPM best practices, the paper concludes with key recommendations for an effective policymaking procedure, dependent on the establishment of an integrated Center of Government in Greece.